Perilaku Hidup Bersih dan Sehat (PHBS) Pada Anak Sekolah - Endah Nurmahmudah; T Puspitasari; I T Agustin (ABDIMAS: Jurnal Pengabdian Masyarakat, 2018)
PHBS stands for clean and healthy living behavior. It is a set of behaviors that are practiced on the basis of awareness in an effort to be healthy and active in helping the healthy of the surrounding environment. PHBS at an early age is very good for educating and instilling awareness of the importance of hygiene as an effort to maintain personal health and the environment. This PKM aims to provide knowledge and understanding of PHBS to students of TK Al-Fadhiilah and the students of SD Cibangunkidul, so that students can practice it in their daily lives. The implementation method was carried out by counseling using in-focus, note-book, and some teaching aids. PHBS counseling for school children went well, all participants were enthusiastic about participating in this PKM activity.